2021
DOI: 10.1038/s41598-021-87293-w
|View full text |Cite
|
Sign up to set email alerts
|

Ileal transposition helps to regulate plasma hepatokine levels in obese Zucker (Crl:ZUC(ORL)-Leprfa) rats

Abstract: We studied the long-term effect of ileal transposition (IT) metabolic surgery on the hepatokines: retinol-binding protein-4 (RBP4), α-2-HS-glycoprotein (aHSG/fetuin-A), and fibroblast growth factor 21 (FGF21), C-reactive protein (CRP) plasma levels, glucose metabolism, body weight, liver histology, as well as total lipids concentration in muscle, liver, and fat tissue of obese Zucker (Crl:ZUC(ORL)-Leprfa) rats. 14 adult males were randomly submitted either to IT or SHAM (control) surgery. Pre-operative hepatok… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 59 publications
0
1
0
Order By: Relevance
“…However, in HFD-fed male Wistar rats, LSG can reduce weight with decreased FGF21 [153]. Consistently, one study reported that three months after ileal transposition metabolic surgery, serum FGF21 levels were lower in obese Zucker rats [154]. Moreover, in research containing 137 obese patients with insulin resistance and high baseline FGF21, FGF21 concentrations were decreased after LSGinduced weight loss.…”
Section: Relationship Between Fgf21 and Obesitymentioning
confidence: 79%
“…However, in HFD-fed male Wistar rats, LSG can reduce weight with decreased FGF21 [153]. Consistently, one study reported that three months after ileal transposition metabolic surgery, serum FGF21 levels were lower in obese Zucker rats [154]. Moreover, in research containing 137 obese patients with insulin resistance and high baseline FGF21, FGF21 concentrations were decreased after LSGinduced weight loss.…”
Section: Relationship Between Fgf21 and Obesitymentioning
confidence: 79%